Identifikasi Hubungan Linier dan Non-Linier antara Rasio-Rasio Keuangan dan Return Saham - I Made Pande Dwiana Putra; I Dewa Nyoman Badera (Akuntabilitas, 2019)
Researches on relevance of financial ratios on stock returns mostly adopt linearity assumptions. This research aims to show the relevance of financial ratios on stock return and to compare the accuracy of linear and  non linear models. Linear and non  linear multivariate regression models are constructed from several financial ratios towards stock return to identify ratios with significant influences and subsequently compared in regard of their determinations. The samples consist of manufacturing companies listed on IDX  from 2009 through 2016 totaling 97 companies. Results of bivariate regressions show consistent relationships exist in form of positive-quadratic relationships for profitability ratios (ROA and ROE) and negative-logarithmic relationships for liquidity and solvability ratios (CR, QR and DER). In general, profitability ratios remain the dominant ratios affecting stock returns